Optical Detection of Protein Adsorption on Doped Titanium Surface - Silvennoinen, Raimo; Penttinen, Niko; Silvennoinen, Martti; Hasoň, Stanislav; Vetterl, Vladimír; Bartáková, Sonia; Prachár, Patrik; Vaněk, Jiří; Březina, Vítězslav (IntechOpen, 2011)
None